Relationship Utilization of Learning Media and Learning Sources with Javanese Learning Outcomes - Pradani, Merinda Sintya; Purnomo, Purnomo (Elementary School Teacher, 2021)
The purpose of this research was to examine the positive and significant relationship between the use of learning media and learning resources with Javanese language learning outcomes fourth grade students of SDN Cluster Melati, Semarang City. This research is a quantitative type of correlation research. The population in this research was the fourth grade students of SDN Gugus Melati, Semarang City. This research amounted to 115 students. Sampling technique using saturated sample. Data collection techniques using question naires, documentation, and interviews. The instrument test was carried out by testing the validity and reliability. Test prerequisite analysis using normality, linearity, and multicollinearity tests. While the data analysis techniques with descriptive statistics, product moment correlation analysis, multiple correlation analysis, significant test, and the coefficient of determination. The results showed that there was a positive and significant relationship between utilization of learning media and learning resources with Java language learning outcomes, variable contribution utilization of learning media and learning resources the learning outcomes are included in the strong category and contribute as much as 40, 9%.Keywords: Learning Outcomes; The use of Learning Media; Learning Resources